The effect of halal foods awareness on purchase decision with religiosity as a moderating variable: A study among university students in Brunei Darussalam. Issue 5 (23rd August 2019) - , Muslichah M.; Abdullah, Rose; Abdul Razak, Lutfi
Abstract : Purpose: The purpose of this paper is to examine the moderating effect of religiosity on the relationship between awareness and purchase decision of halal foods. Design/methodology/approach: Using a convenience sampling procedure, 200 questionnaires were distributed to various local higher education institutions with a 64% response rate. A moderated regression analysis is used to test the relationship between awareness and purchase decision, with religiosity as the moderating variable. Findings: As expected, the authors find that among the sample, the level of awareness toward halal foods is high, and that the effect of awareness on purchase decision is positive and significant. Importantly, they find that religiosity acts as a moderating variable on the relationship between awareness and purchase decision. Research limitations/implications: First, the sample was taken from higher institutions only and respondents were selected using convenience sampling. Hence, it may not be fully representative of the Brunei Muslim population. Second, there may also be omitted variables not considered in the study. Third, the survey instrument and conceptualization of religiosity are both issues that may require further investigation in the literature. Practical implications: The results indicate that awareness is an important antecedent of Muslim students' intention to purchase halal foods. Marketers should design their campaigns focusing on creating awareness regarding their compliance with halal products. Moreover, food manufacturers and sellers should use the reliable halal certification and logo as a way to inform their consumers that their products are truly halal . Originality/value: This study adds to the current limited knowledge of halal foods research. In particular, the authors investigate the moderating effect of religiosity on the relationship between awareness and purchase decision of halal foods.